2008
DOI: 10.1182/blood-2007-07-100677
|View full text |Cite
|
Sign up to set email alerts
|

Furin-mediated release of soluble hemojuvelin: a new link between hypoxia and iron homeostasis

Abstract: The liver peptide hepcidin regulates iron absorption and recycling. Hemojuvelin (HJV) has a key role in hepcidin regulation, and its inactivation causes severe iron overload both in humans and in mice. Membrane HJV (m-HJV) acts as a coreceptor for bone morphogenetic proteins (BMPs), whereas soluble HJV (s-HJV) may down-regulate hepcidin in a competitive way interfering with BMP signaling. s-HJV is decreased by iron in vitro and increased by iron deficiency in vivo. IntroductionThe liver peptide hepcidin is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
280
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(296 citation statements)
references
References 35 publications
9
280
2
5
Order By: Relevance
“…We find that BMP-2 binds to RGMc as effectively as to noggin, a known high-affinity BMP-interacting molecule (39,43), and detect a preference of BMP-2 for single-chain RGMc, particularly the 40-kDa species, which is derived from cleavage of 50-kDa RGMc by proprotein convertases (20,40). Our results thus extend the observations of Babitt et al (2), who used protein cross-linking and competition binding assay to establish an association between I 125 -labeled BMP-2 and an RGMc-IgG Fc fusion protein, and those of Halbrooks et al (9), who showed using surface plasmon resonance that soluble RGMc could bind BMP-2 with nanomolar affinity (9).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We find that BMP-2 binds to RGMc as effectively as to noggin, a known high-affinity BMP-interacting molecule (39,43), and detect a preference of BMP-2 for single-chain RGMc, particularly the 40-kDa species, which is derived from cleavage of 50-kDa RGMc by proprotein convertases (20,40). Our results thus extend the observations of Babitt et al (2), who used protein cross-linking and competition binding assay to establish an association between I 125 -labeled BMP-2 and an RGMc-IgG Fc fusion protein, and those of Halbrooks et al (9), who showed using surface plasmon resonance that soluble RGMc could bind BMP-2 with nanomolar affinity (9).…”
Section: Discussionmentioning
confidence: 86%
“…Membrane-associated RGMc consists of both a single-chain 50-kDa polypeptide and a disulfide-bonded heterodimer composed of 20-kDa NH 2 -terminal and 35-kDa COOH-terminal subunits (15,19,41,48), while soluble RGMc consists of 50-and 40-kDa species that are derived from the membrane-bound 50-kDa protein (15). Although the responsible biochemical mechanisms have not been elucidated fully, it appears that 40-kDa soluble RGMc is truncated at its COOH terminus through cleavage by proprotein convertases (20,40).…”
mentioning
confidence: 99%
“…2 The central role of HJV in body iron homeostasis is supported by the evidence that Hjv knockout mice (Hjv -/-mice) show severe suppression of hepatic hepcidin and increased iron deposition in the liver, pancreas and heart. 3,4 HJV encodes a protein characterized by a N-terminal signal peptide, a RGD integrin binding motif, a partial von Willebrand factor type D domain containing a glucose-6-phosphate dehydrogenase (GDPH) consensus sequence for autoproteolysis, a RNRR consensus sequence for furin cleavage 5,6 and a C-terminal GPI-anchor domain.…”
Section: Introductionmentioning
confidence: 99%
“…s-HJV acts as an antagonist in the hepcidin activation pathway, sequestering BMP and interrupting their signaling. 10 Large amounts of s-HJV are released into cellular media in conditions of iron deficiency 6 and this soluble protein is reduced in conditions of iron overload.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the serine protease matriptase-2 (TMPRSS6) binds and cleaves cell surface RGMc. However, the RGMc fragment shed by matriptase-2 has reduced ability to bind BMPs and fails to repress BMPinduced hepcidin expression in vitro [40,41]. Unlike furin, it is thought that matriptase-2 impacts iron homeostasis mainly by reducing levels of membrane-bound RGMc.…”
Section: Autocatalytic and Proteolytic Cleavage Of Rgmc In The Contromentioning
confidence: 99%